Changing age-specific trends in incidence, comorbidities and mortality of hospitalised heart failure in Western Australia between 2001 and 2016. (15th November 2021) - Weber, Courtney; Hung, Joseph; Hickling, Siobhan; Li, Ian; Murray, Kevin; Briffa, Tom
Abstract: Background: Incident heart failure (HF) hospitalisation rates in most high-income countries are stable or declining. However, HF incidence may be increasing in younger people linked to changing risk factor profiles in the general population. We examined age and sex-specific patterns of incidence, comorbidities and mortality of hospitalised HF in Western Australia (WA) between 2001 and 2016. Methods and results: All WA residents aged 25–94 years, with an incident (first-ever) principal HF discharge diagnosis between 2001 and 2016 were included ( n  = 22, 476). Poisson regression derived annual age and sex-standardised rates of incident HF and 1-year mortality overall, and by age groups (25–54, 55–74, 75–94), across the study period. Overall, the age and sex-standardised rates of incident HF increased marginally by 0.6% per year (95% confidence interval (CI), 0.3, 0.8) whereas incidence increased by 3.1% per year (95% CI, 2.2, 4.0) in the 25–54 year age-group (trend p  < 0.0001). There was a high prevalence (≥15%) of obesity, diabetes mellitus, cardiomyopathy, hypertension, ischemic heart disease, atrial fibrillation, and chronic kidney disease in younger HF patients. Overall standardised 1-year mortality declined by −1.0% per year (95%CI, −0.4, −1.6), driven largely by the mortality decline in the 55–74 year age group. Conclusion: Incident HF hospitalisation rates have been rising in WA since 2006, notably in individuals under 55 years. The underlying reasons require further investigation, particularly the population-attributable risk related to increasing obesity and diabetes mellitus in the general population. Rising HF incidence along with declining mortality rates portends to an increasing HF burden in the community. Highlights: Incident HF hospitalisations are increasing, particularly in people under 55 years. Comorbidities, like diabetes and obesity, may be driving these trends. Rising incidence along with declining mortality portends to an increasing HF burden.